2007
DOI: 10.1139/t06-125
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation-induced cracking and its effect on the hydraulic conductivity of clayey soils from Iran

Abstract: Clay materials have many environmental applications, especially in situations where a hydraulic barrier is desired. However, as the plasticity of clay increases, cracks tend to develop during cycles of long dry spells. This is particularly a concern in the construction of covers or installation of landfill liners prior to waste filling. In the present study, specimens prepared from three natural clayey soils from Iran used for clay barrier construction, and one artificial clayey soil, were subjected to cycles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(47 citation statements)
references
References 7 publications
0
45
1
1
Order By: Relevance
“…Desiccation of the topmost fraction occurs relatively quickly and induces the formation of surface cracks due to shrinkage from water evaporation. This results in changes to the material permeability and exposes additional material for drying, though some clay minerals are able to self-repair desiccation cracks when subjected to moisture (Rayhani, et al, 2007). However, material fractions at depths of more than ~0.5 m do not experience significant natural drying even after a prolonged period of time, as demonstrated by Masala and Dhadli (2012).…”
Section: Evaporative and Thermal Treatmentsmentioning
confidence: 99%
“…Desiccation of the topmost fraction occurs relatively quickly and induces the formation of surface cracks due to shrinkage from water evaporation. This results in changes to the material permeability and exposes additional material for drying, though some clay minerals are able to self-repair desiccation cracks when subjected to moisture (Rayhani, et al, 2007). However, material fractions at depths of more than ~0.5 m do not experience significant natural drying even after a prolonged period of time, as demonstrated by Masala and Dhadli (2012).…”
Section: Evaporative and Thermal Treatmentsmentioning
confidence: 99%
“…The results from Rayhani et al (2007) showed that the dimension of cracks increased with increasing plasticity index and clay content and so, the initial hydraulic conductivity increased with increasing plasticity index and cycles of drying and wetting. Nahlawi and Kodikara (2006) carried out some experiments on the induced cracking tests on thin layers of clay soils using humidity and temperature controlled chamber for observation, crack initiation and evolution and for moisture content measurement during desiccation.…”
Section: Introductionmentioning
confidence: 98%
“…Albrecht and Benson (2001) found that the hydraulic conductivity of some clay liner materials caused by desiccation cracks was almost 500 times that of intact soil. The experiments of Boynton and Daniel (1985) and Rayhani et al (2007) showed that soil cracking increases the hydraulic conductivity of several orders of magnitude. In addition, these cracks induced by shrinkage also create weak zones in a soil body with reduced overall mechanical strength and bearing capacity, and increased compressibility.…”
Section: Introductionmentioning
confidence: 99%